The Development of Urban Farming: Systematics Literature Review - Dalimunthe, Maulana Andinata; Ohorella, Noviawan Rasyid; Nasution, Nabila Fahira (Talenta Publisher, 2023)
The development of urban farming continues to grow, encouraging the emergence of a joint movement in creating food security, building the environment, economy, and community empowerment. This development trend has also made urban farming one of the leading programs in building food security. This research aims to understand the relevance of urban farming development. The method used is bibliometric analysis in looking at the development of research with the keyword